The influence of environmental certification and waste management practices on tourist preferences at green hotels in Bandung - Jimmy Ruben Sihombing; Kurniawan Saefullah; Edwin Rizal (Education and Development Research, 2026)
Tourism sector growth in Bandung City has shown significant improvement in the post-pandemic period, accompanied by increasing tourist awareness of sustainability issues. Despite this trend, environmentally friendly practices are not yet consistently implemented across all hotels. This study aims to analyze the influence of environmental certification and waste management practices on tourists’ preferences for green hotels in Bandung City. A mixed-methods approach was employed using surveys of 25 tourists who had stayed at green hotels. Quantitative data were analyzed using multiple linear regression, and qualitative data through thematic analysis. The results indicate that both environmental certification and waste management practices positively influence tourists’ preferences. Certifications such as CHSE, Green Globe, and ISO 14001 enhance tourists’ trust in a hotel’s commitment to sustainability, while concrete practices, including recycling programs, reduction of single-use plastics, and food donation initiatives, strengthen perceptions of environmental responsibility. However, the limited sample size (N = 25) reduces the statistical power and external validity of the quantitative findings, positioning the results as exploratory rather than conclusive. Nonetheless, the qualitative findings provide valuable insights, revealing that tourists are willing to pay a premium, demonstrate loyalty, and recommend green hotels that align with their environmentally conscious lifestyles. These findings emphasize the importance for hotels not only to obtain environmental certification but also to implement tangible ecological practices that deliver measurable environmental benefits. Overall, this study contributes empirical evidence on how environmental initiatives can simultaneously enhance tourist engagement and support sustainable tourism development, reinforcing the role of hotels as both economic actors and agents of environmental stewardship.